Postoperative Tonsillectomy Pain Management: A Prospective Randomized Trial. (23rd August 2013) - Standring, Robert T.; Guglielmo, Robert; Yaremchuk, Kathleen L.; Gardner, Glendon M.; Ko, Alvin B.; Seidman, Michael D.; Darrat, Ilaaf
Abstract : Objectives: Examine the efficacy of three separate pain regimen groups for patients who have undergone tonsillectomies by multiple otolaryngologic surgeons at one institution. Methods: This study was an institutional review board (IRB) approved prospective randomized cohort study comparing the efficacy of nonsteroidal anti‐inflammatory drugs (NSAIDs), acetaminophen/hydrocodone, and acetaminophen/codeine for post‐operative tonsillectomy pain control. Setting: A tertiary referral hospital. Patients of any age undergoing tonsillectomy from June 2011 until the present were randomized into one of three post‐op pain regimen groups. All tonsillectomy procedures were performed using the same technique, no preoperative local anesthetic injections were given, and no post‐operative antibiotics were provided. Patients/families were given a packet of information to complete that included pain control, time to return to diet, school/work, and baseline activity. Pain control was measured using a validated faces pain scale as well as the amount of drug being administered. Results: Eighty‐five patients were enrolled in the study, and twenty‐four patients completed the study packet: 11 patients from the ibuprofen arm, 7 patients from the acetaminophen/hydrocodone arm, and 6 patients from the acetaminophen/codeine arm. The preliminary data were analyzed with Kruskal‐Wallis tests and demonstrated no significant difference in time to return to regular diet (p =0.867), time to return to work (p=0.849), or time to return to work/school (p=0.915). Conclusions: These preliminary results demonstrate efficacy of all three pain modalities with no significant difference in returning to pre‐operative function.